Load transfer mechanism of concrete screws - Florian Stocker; Oliver Zeman; Michael Schwenn; Konrad Bergmeister (Acta Polytechnica CTU Proceedings)
Even though the market and development for concrete screws has been increasingly rising in recent years, the load transfer mechanism of concrete screws has not yet been fully investigated. Therefore, different tests of concrete screws made of galvanized and stainless steel were performed in concrete C20/25 and C50/60. The main aim is to measure the strain along the embedment depth. This will be achieved by using strain gauges that get placed in a centrically drilled borehole through the concrete screw. To get a comparison to the mechanism of the screws the same process will be executed in threaded rods used as a part of bonded anchors. Due to the fact that the threaded cuts of concrete screws have geometrical similarities to bonded anchors, it was examined if the load transfer of both fasteners is related and may be compared. The results of the testing have shown that the load transfer mechanism of both fastener types is similar in low-strength concrete showing a concrete cone failure. In high strength concrete due to the mainly occurring steel failure the maximum measured strains at the maximum load step are not comparable. However, at lower load steps where the steel does not exceed the yield strength the results show a similar load transfer mechanism, too.